Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's walk through the process of solving the equation step-by-step:
We are given the equation:
[tex]\[ 2\left(\frac{1}{49}\right)^{x-2} = 14 \][/tex]
1. Isolate the exponential term:
First, divide both sides of the equation by 2 to isolate the exponential expression:
[tex]\[ \left(\frac{1}{49}\right)^{x-2} = 7 \][/tex]
2. Rewrite the exponential term:
Recall that [tex]\(\frac{1}{49}\)[/tex] can be written as [tex]\(49^{-1}\)[/tex]. So the equation becomes:
[tex]\[ (49^{-1})^{x-2} = 7 \][/tex]
Which simplifies to:
[tex]\[ 49^{-(x-2)} = 7 \][/tex]
3. Express 7 as a power of 49:
We recognize that [tex]\(7^2 = 49\)[/tex]. Therefore, [tex]\(7 = 49^{1/2}\)[/tex]. Substituting this into the equation:
[tex]\[ 49^{-(x-2)} = 49^{1/2} \][/tex]
4. Set the exponents equal to each other:
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ -(x-2) = \frac{1}{2} \][/tex]
5. Solve for [tex]\(x\)[/tex]:
Simplify the equation to get:
[tex]\[ -(x - 2) = \frac{1}{2} \][/tex]
Distribute the negative sign:
[tex]\[ -x + 2 = \frac{1}{2} \][/tex]
Subtract 2 from both sides:
[tex]\[ -x = \frac{1}{2} - 2 \][/tex]
Simplify the right-hand side:
[tex]\[ -x = \frac{1}{2} - \frac{4}{2} = -\frac{3}{2} \][/tex]
Finally, multiply both sides by -1:
[tex]\[ x = \frac{3}{2} \][/tex]
Thus, the solution to the equation is:
[tex]\[ x = \frac{3}{2} \][/tex]
Therefore, the correct answer is [tex]\(\boxed{\frac{3}{2}}\)[/tex].
We are given the equation:
[tex]\[ 2\left(\frac{1}{49}\right)^{x-2} = 14 \][/tex]
1. Isolate the exponential term:
First, divide both sides of the equation by 2 to isolate the exponential expression:
[tex]\[ \left(\frac{1}{49}\right)^{x-2} = 7 \][/tex]
2. Rewrite the exponential term:
Recall that [tex]\(\frac{1}{49}\)[/tex] can be written as [tex]\(49^{-1}\)[/tex]. So the equation becomes:
[tex]\[ (49^{-1})^{x-2} = 7 \][/tex]
Which simplifies to:
[tex]\[ 49^{-(x-2)} = 7 \][/tex]
3. Express 7 as a power of 49:
We recognize that [tex]\(7^2 = 49\)[/tex]. Therefore, [tex]\(7 = 49^{1/2}\)[/tex]. Substituting this into the equation:
[tex]\[ 49^{-(x-2)} = 49^{1/2} \][/tex]
4. Set the exponents equal to each other:
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ -(x-2) = \frac{1}{2} \][/tex]
5. Solve for [tex]\(x\)[/tex]:
Simplify the equation to get:
[tex]\[ -(x - 2) = \frac{1}{2} \][/tex]
Distribute the negative sign:
[tex]\[ -x + 2 = \frac{1}{2} \][/tex]
Subtract 2 from both sides:
[tex]\[ -x = \frac{1}{2} - 2 \][/tex]
Simplify the right-hand side:
[tex]\[ -x = \frac{1}{2} - \frac{4}{2} = -\frac{3}{2} \][/tex]
Finally, multiply both sides by -1:
[tex]\[ x = \frac{3}{2} \][/tex]
Thus, the solution to the equation is:
[tex]\[ x = \frac{3}{2} \][/tex]
Therefore, the correct answer is [tex]\(\boxed{\frac{3}{2}}\)[/tex].
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.